Semantic Analysis of the Figurative Expressions Used in the Text Sati Quits Her Body - Dewi Yulianti, Ni Ketut; Sumerjana, Ketut; Sudibya, I Gusti (International Seminar on Austronesian Languages and Literature; Vol 9 No 1 (2021): PROCEEDINGS International Seminar on Austronesian Languages and Literature IX (ISALL IX), 2021)
A discussion of types of figurative expression and their meanings in the text Sati Quits Her Body is presented in this paper.  It will be useful not only for language teachers who are engaged in text but also for artists who love to use figurative language in their performances. This topic is very significant to be researched because the text is a religious text that contains figurative expressions with their moral values. The meanings of the figurative expressions cannot be separated from the theme of the text. The method used is a qualitative method by analyzing the text attentively to find out the types of figurative expressions used in the text. Analyzing the theme of the text is conducted before analyzing the meaning of each figurative expression used in the text. Theoretically, this paper can provide an understanding of a religious text, especially regarding the message contained in it. Practically, this paper can contribute to the world of education so that it can help in increasing the understanding of religious text and moral values